Designing a Digital Marketing Strategy for UMKM Batik Jati Kusuma using the Sostac Method - Krisbiantoro, Dwi; Sarmini, Sarmini; Rahmah, Anisa Aulia (International Journal of Informatics and Information Systems, 2023)
Batik Jati Kusuma is an MSME that produces various types of batik cloth. Its product marketing technique, Batik Jati Kusuma, still uses conventional techniques so that the marketing process is not optimal. In order for the product marketing process to run optimally, it is necessary to design a special strategy. The purpose of this study is to expand the marketing area by implementing digital marketing designs on social media platforms in the form of Facebook ads and Instagram ads using the SOSTAC method combined with SWOT analysis and Value Proposition Canvas. The results of the SWOT analysis obtained 4 predictions, where the main strength lies in the selling price of batik cloth products which are cheap so that they are easily accessible to the public, while the weakness lies in the sales process using conventional techniques, these MSME must implement marketing strategies using social media in the form of Facebook ads and Instagram ads to reach broad target consumers, the main opportunity is to be able to form a batik brand image typical of Karangjati village. Then the main threat is the emergence of new, similar competitors, so these MSME must create superiority and competitiveness in their products. From the SWOT results, the percentage on Facebook ads increased by 84%, then the percentage on Instagram ads increased by 80%.